Pengaruh Pengetahuan Akuntansi Pelaku UMKM terhadap Penggunaan Informasi Akuntansi di Kabupaten Tegal - Maratussolikhah Maratussolikhah; Nurul Wulandari Putri (Universitas 45 Surabaya, 2025)
This study aims to analyze the influence of accounting knowledge on the level of use of accounting information in business decision-making by micro, small, and medium enterprises (MSMEs) in Tegal Regency. Using a quantitative approach through the survey method, as many as 53 MSMEs were randomly selected as samples. Data collection was carried out through a structured questionnaire, then analyzed using simple linear regression to test the relationship between accounting knowledge variables and the use of accounting information. The results of the analysis show that accounting knowledge has a positive and significant influence on the use of accounting information. MSMEs that have a better understanding of accounting principles tend to be more active and effective in utilizing accounting information to support the business decision-making process. These findings affirm the importance of increasing accounting literacy among MSME actors as a strategy to strengthen competitiveness and business sustainability. This research provides practical contributions for policymakers and MSME companion institutions in designing a more targeted accounting training program. In addition, the results of this study also open up opportunities for further research that explores other variables that affect the effectiveness of business decision-making in the MSME sector.